A Reader Response to the Basic Needs Budget - Staff, Editorial (Maine Policy Review, 1996)
This commentary presents a thoughtful, personal illustration of the basic needs budget approach in response to an article by Stephanie Seguino published in Maine Policy Review in October 1995. The basic needs budget approach originally was designed to more accurately measure household economic status than the official poverty measure. The intent is to provide a series of budgets that describe the amount of income required by “self-sufficient” households to meet basic needs. As this reader’s analysis so aptly demonstrates, more generalized use of a basic needs budget approach would in fact require the development of a series of baseline budgets for households of different sizes and age compositions. Further, defining self-sufficiency would require consideration of all household sources of revenue and expenditure in order to obtain an accurate assessment of household economic status.
Keywords: Maine; basic needs budget; livable wage